Risk Management Approach in Facing Market Uncertainty for MSMEs in the Culinary Industry - Afrizal Afrizal; Friend Zakharia; Nazrantika Sunarto; Romualdus Antonius Geli Koten; Helmi Ali (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study explores how culinary MSMEs in Indonesia implement risk management strategies to cope with market uncertainty influenced by fluctuating consumer demand, digital competition, rising production costs, and unstable supply chains. Employing a qualitative descriptive approach, the research gathered data through interviews, observations, and document reviews involving purposively selected MSME owners. The results show that most culinary MSMEs adopt informal, experience-driven practices to manage risks, focusing on product flexibility, diversified suppliers, cost-control efforts, and proactive digital engagement. The use of social media, online delivery services, and electronic payment systems supports wider customer reach, operational continuity, and more predictable transactions, even though digital literacy limitations and resource constraints continue to hinder optimal adoption. Comparative findings from Surabaya, Bandung/Soreang, Denpasar, Malang, and Sleman/Yogyakarta indicate that MSMEs across regions face similar risk patterns and apply comparable adaptive strategies, suggesting that these issues are structural rather than geographically unique. Overall, the study highlights that resilience among culinary MSMEs is strengthened by agility, practical decision-making, and effective utilization of digital tools. It also points to the importance of expanded institutional support, capability-building initiatives, and accessible risk management frameworks tailored to the needs of micro-enterprise actors.